Evaluation of families of a Psychosocial Attention Center of the south area of brazil: a methodological proposal - Wetzel, Christine; de Pinho, Leandro Barbosa; Schwartz, Eda; Lange, Celmira; Kantorski, Luciane Prado; Zillmer, Juliana (Online Brazilian Journal of Nursing, 2010)
<!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.MsoBodyTextIndent3, li.MsoBodyTextIndent3, div.MsoBodyTextIndent3 mso-style-unhide:no; mso-style-link:"Recuo de corpo de texto 3 Char"; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:54.0pt; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; tab-stops:54.0pt; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; font-weight:bold; span.Recuodecorpodetexto3Char mso-style-name:"Recuo de corpo de texto 3 Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Recuo de corpo de texto 3"; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; font-weight:bold; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Objective: to present a methodological proposal of evaluation of users’ of a Psychosocial Attention Center (CAPS), developed in a wider research of evaluation of CAPS of the South Area of Brazil (States of Rio Grande do Sul, Santa Catarina and Paraná). Method: it is a case study, with evaluative approach, accomplished in a CAPS of the State of Santa Catarina. It was developed with the methodology of Fourth Generation Evaluation, constructivist, responsive and with hermeneutic-dialectic approach. The evaluation of families was accomplished with the aid of Calgary Family Assessment Model (CFAM), with the genogram and ecomap. Results: CFAM provided the understanding of the family organization, to visualize the potentialities and fragilities of the family and this social network. Conclusion: the used methodology contributes to the qualification of the interventions, especially the care of the person with psychic disorders and his family.